Electroweak Precision Measurements: Present and Future - Nascimento, Fernanda Hüller (2020)
Thanks to the work of thousands of physicists over the past 80 years, we now have a remarkable understanding of how nature behaves at high energies. Everything in the Universe, from the most distant quasar to the smallest atom, is made of what we call fundamental particles. These particles are governed by four different forces: strong, weak, electromagnetic and gravitational. Developed in the early 1970s, the so-called Standard Model of particle physics is capable of describing how particles are related to three of these forces. Since it was first proposed, the Standard Model has successfully explained several experimental results to an outstanding precision, and correctly predicted the existence of many new particles, including the famous Higgs boson. However, even though it is currently our best description of the subatomic world, the Standard Model does not explain the complete picture. One major problem is that the theory fails to describe gravity and to answer why this fundamental force is much weaker than the others. Another big difficulty is what physicists call the hierarchy problem, which refers to the sensitivity of the Higgs mass to new scales. Besides these two, there are many other questions left unanswered by the Standard Model, such as the matter-antimatter asymmetry, the nature of dark matter and dark energy, the strong CP problem, and the mass of neutrinos. Thus, it became clear there must be new physics hidden deep in the Universe. In the past few years, physicists have dedicated themselves to the development of different extensions of the Standard Model. Since precision experiments have been crucial in establishing the validity of our current description, they will also be instrumental to assess whether new physics is already manifesting itself in experimental data. Focusing on the phenomenological constraints that precision measurements can provide on the gauge sector of the electroweak group, we aim to pursue a new precision program in which the most generic modifications due to new physics will be considered. We intend to apply this formalism to theories that extend the Standard Model gauge symmetry by a new Abelian group called U(1)X. The gauge boson associated with U(1)X can mix with both the Standard Model Z boson and photon through the kinetic term. Furthermore, depending on how we choose to break this extra symmetry, the new gauge boson X can also have a mass mixing with them. As we will show, such mixings imply in three new eigenstates. The photon and Z boson we observe are now a mixture of the Standard Model fields and the X boson field. The same is true for the third observable eigenstate, which is known as Z\' boson. In this work, we propose the Z\' to be in the MeV-GeV mass range. Such mass range has been of great interest to physicists since they realized new particles can be quite light and still have evaded discovery in particle accelerators. Modifications of electroweak observables due to the presence of a light Z\' boson have not been studied systematically in the literature to date. Thus, our analysis consists in performing a global fit to the W boson mass and other eleven observables measured at the Z resonance. This allows us to determine an exclusion region in the parameter space of our model, and establish the mass range of the Z\' boson consistent with current experimental data. Finally, we can check whether our model is able to explain the tension between the theoretical and experimental values of the muon magnetic moment. Such discrepancy is now considered one of the most stringent constraints on potential new physics effects.